2010
DOI: 10.1007/s00439-010-0894-4
|View full text |Cite
|
Sign up to set email alerts
|

Sperm rates of 7q11.23, 15q11q13 and 22q11.2 deletions and duplications: a FISH approach

Abstract: Genomic disorders are human diseases caused by meiotic chromosomal rearrangements of unstable regions flanked by Low Copy Repeats (LCRs). LCRs act as substrates for Non-Allelic Homologous Recombination (NAHR) leading to deletions and duplications. The aim of this study was to assess the basal frequency of deletions and duplications of the 7q11.23, 15q11-q13 and 22q11.2 regions in spermatozoa from control donors to check differences in the susceptibility to generate anomalies and to assess the contribution of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…The 22q11.2 deletion syndrome has been reported as the most common deletion syndrome [4,9]. With the use of MLPA, molecular cytogenetic and cytogenomic methods, we observed that two unrelated patients (A and D) had this syndrome, both carrying a 2.5 Mb deletion of the 22q11.2 region.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The 22q11.2 deletion syndrome has been reported as the most common deletion syndrome [4,9]. With the use of MLPA, molecular cytogenetic and cytogenomic methods, we observed that two unrelated patients (A and D) had this syndrome, both carrying a 2.5 Mb deletion of the 22q11.2 region.…”
Section: Discussionmentioning
confidence: 88%
“…These structural variants are strongly associated with genetic syndromes [1]. The most common example is the 22q11.2 deletion syndrome, which is estimated to affect approximately 1 in 4000 live births [4] and results most commonly from a 3 Mb deletion in the 22q11.2 region [4-7]. This region contains approximately 40 genes [8], being the TBX1 and COMT the most relevant [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we clearly demonstrate that the proband in family 1 had homozygous duplications in the typical DGS region with one duplication inherited, and the other a de novo event during spermatogenesis. A study suggested that interchromatid NAHR is the predominant mechanism involved in the generation of sperm deletions and duplications 27. Consistently, this de novo duplication was most likely generated through a paternal interchromosomal NAHR between LCRs.…”
Section: Discussionmentioning
confidence: 93%
“…The reciprocal duplication is observed at a lower frequency. By sperm typing, Molina et al [2011] determined genotypic frequencies of 0.17 ± 0.2% for the deletion and 0.12 ± 0.03% for the duplication. The difference can be explained by the causal mechanisms of the deletion and duplication.…”
mentioning
confidence: 99%